Growth Response and Production of Sweet Corn (Zea mays L. saccharata Sturt) Perkasa F1 Variety with Application of POC and Humic Acid - Nunuk Helilusiatiningsih; Karina Oktaviani; Nur Fitriyah (Formosa Journal of Science and Technology, 2022)
The purpose of this study was to determine the growth response and production of sweet corn (Zea mays L.  saccharata Sturt) variety Perkasa F1 with the application of LOF and humic acids. This research was carried out in March-June 2022 at a location in Donganti Village, Plosoklaten District, Kediri Regency with an altitude of ± 60 meters above sea level and a  pH of 6.8.  The experimental method used is RCBD. The first factor is LOF (P) consisting of 5 levels: control, 50 ml / l, 75 ml / l, 100 ml / l, 125 ml / l. The second factor is humic acids (A) consists of 4 levels: control, 5 kg / ha, 10 kg / ha, 15 kg / ha.  Data analysis using analysis of variance tables (ANOVA) by advanced test of Least Significant Difference (LSD) 5%. The results showed that the application of the combination of LOF and humic acids gave a very significant effect on plant height of 35 DAP, and stem diameter of 35 DAP and also gave significant effect on the number of leaves of 35 DAP, stem diameter of 35 DAP, weight of cobs with cornhusk. The application of humic acids at a dose of 10 kg/ha shows significant effect on the ingratiating levels.